Tax morale and taxpayer compliance in West Sumatra: Empirical evidence via Partial Least Squares Structural Equation Modelling (PLS-SEM). - Adriansyah; Ismail, Zuriadah; Ahmad, Anis Suriati; Hashim, Asmawi (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the effect of tax morale on tax compliance in the Indonesian self-assessment system, with a regional focus on West Sumatra. Drawing on the psychological tax contract and the slippery slope model, the study analyzes the relationship between tax knowledge and tax behaviour using data from 363 taxpayers within the framework of Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings support the psychological tax contract framework and confirm the importance of psychological factors, indicating that tax morale is a significant predictor of tax compliance. In particular, tax morale is found to have a strong effect on compliance, while tax knowledge also exerts a positive influence. The results suggest that policy interventions should focus on increasing voluntary compliance by prioritizing measures that build institutional trust, encourage civic participation, and enhance transparency in the use of public funds, alongside targeted technical tax education. Emphasizing ethical and trust‑building strategies is likely to yield greater improvements in tax compliance than technical instruction alone.